Sugarcane (Saccharum species) research in the post-Independence era - MISRA, S R; SHRIVASTAVA, A K (The Indian Journal of Agricultural Sciences, 2013)
Since Indcpendence, commendable progress has been made in most of the areas of sugarcane (Saccharum sp) research vis-a-vis establishment of a strong research infrastructure which has not only improved the crop productivity per se butÂ· also augmented our knowledge about sugarcane. A large number of outstanding sugarcane varieties were developed which are sustaining sugar industry. Commendablc research work was done on cytogenetics, mutations, inter-specific hybrids, etc. From crop production point of view, plimting techniques, viz IISR 8626, spaced transplanting (STP), bud-chip method, polythene bag nursery (for lateplanted conditions), system of trash veins (for salt-affected soils) etc showed promise. Concerted efforts were made in economizing water use and improving water-usc efficiency. Research efforts were made to improve the productity of sugarcane planted after wheat harvest under north Indian conditions. Studies in sugarcane physiology have led to understanding of growth and development, photosynthesis, response to abiotic and biotic stresses, sugar accumulation arresting post-harvest deterioration and development of technology to induce ripening under difficult to ripen conditions. Mechanization of sugarcane culture appears to be the only solution to labo,ur scarcity, reduCing cost of cultivarion and performing cultural operations timely, so as to improve productivity per unit time, area and energy. Some useful implements were developed in the country. A good deal of research work was done on various aspects of sugarcane diseases, insect-pests and their management. An mtegrated pest-management strategy against insect pests and diseases has been developed. Future lines of research work have been suggested which will go a long way in improving the sugarcane and sugar productivity per unit time, area and energy, so as to cater to the increasing demands for sweetening agents and other value-added products, of the burgeoning population, in times to come.